Enriched environment and visual stimuli protect the retinal pigment epithelium and photoreceptors in a mouse model of non-exudative age-related macular degeneration - Dieguez, Hernán H. (2021)
Fil. Dieguez, Hernán H. Universidad de Buenos Aires. Facultad de Medicina. Departamento de Bioquímica Humana. Laboratorio de Neuroquímica Retiniana y Oftalmología Experimental; Argentina